2015
DOI: 10.1155/2016/5710403
|View full text |Cite
|
Sign up to set email alerts
|

The Cellular Response to Oxidatively Induced DNA Damage and Polymorphism of Some DNA Repair Genes Associated with Clinicopathological Features of Bladder Cancer

Abstract: Genome instability and impaired DNA repair are hallmarks of carcinogenesis. The study was aimed at evaluating the DNA damage response in H2O2-treated lymphocytes using the alkaline comet assay in bladder cancer (BC) patients as compared to clinically healthy controls, elderly persons, and individuals with chronic inflammations. Polymorphism in DNA repair genes involved in nucleotide excision repair (NER) and base excision repair (BER) was studied using the PCR-RFLP method in the Belarusian population to elucid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 71 publications
2
11
0
2
Order By: Relevance
“…MUTYH has a functional role of repairing 8-hydroxyguanine mismatches that occur as a result of adenine glycosylase activity (Slupska, Luther, Chiang, Yang, & Miller, 1999). A previous study indicated that the homozygous CC genotype of rs3219489 was associated with an increased risk of CRC when compared to the GG genotype (Picelli et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MUTYH has a functional role of repairing 8-hydroxyguanine mismatches that occur as a result of adenine glycosylase activity (Slupska, Luther, Chiang, Yang, & Miller, 1999). A previous study indicated that the homozygous CC genotype of rs3219489 was associated with an increased risk of CRC when compared to the GG genotype (Picelli et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…However, DNA repair genes are polymorphic, and the single nucleotide polymorphism (SNP) of these genes is associated with cancer development (Moreno et al., ). Polymorphisms of MLH1 , APEX1 , MUTYH , OGG1 , NUDT1 , and XRCC5 are associated with sporadic CRC (Kim et al., ; Lai et al., ; Yang et al., ) and other site‐specific cancers (Li et al., ; Savina et al., ; Smith et al., ). However, recent studies have indicated that XPA and ERCC2 SNPs are not associated with sporadic CRC (Chang et al., ; He, Deng, & Luo, ).…”
Section: Introductionmentioning
confidence: 99%
“…An interpretation in terms of cancer susceptibility seems not to be reasonable (Collins and Azqueta 2012). Nevertheless, accumulation of oxidatively induced DNA damage might serve as a potential biomarker of genome instability predisposing to cancer as recently shown by comparing the damage response in H 2 O 2 -treated lymphocytes using the comet assay in bladder cancer patients as compared to healthy controls, elderly persons, and individuals with inflammations (Savina et al 2016).…”
Section: Dna Repairmentioning
confidence: 99%
“…Some excision repair gene polymorphisms modify the susceptibility to bladder cancer. For example, polymorphisms (codons 312 and 751) in xeroderma pigmentosum group D (XPD) gene increase cancer risk, whereas a combination of homozygous wild-type genotypes were associated with a twice lower frequency in T ≥ 2 carcinomas suggesting that the maintenance of normal DNA repair activity seems to inhibit cancer initiation and/or cancer progression (Savina et al 2016). …”
Section: Oxidative Damagementioning
confidence: 99%
“…Нами ранее было показано, что некоторые полиморфизмы генов эксцизионной репарации оснований (OGG1 rs1052133 и XRCC1 rs25487) и нуклеотидов (ERRC2/XPD rs1799793 и ERRC6/CSB rs2228526) модифицируют предрасположенность к раку мочевого пузыря [2], а также ассоциированы с клинико-патологическими характеристиками заболевания [3][4][5]. Кроме того, установлено, что дикие аллели генов ERCC2/XPD (rs1799793, rs13181) и ERCC6/CSB (rs2228526, rs2228528) благоприятствуют долгожительству, уменьшают риск развития РМП (особенно после 80 лет) у их носителей, а также ассоциированы с низкой степе-нью распространенности и злокачественности опухоли, редким рецидивированием [6].…”
unclassified